2011
DOI: 10.5152/akd.2011.158
|View full text |Cite
|
Sign up to set email alerts
|

The particular interactions of the traditional cardiovascular risk factors with different circulating specific leukocyte subtype counts in blood: an observational study

Abstract: Objective: The pathogenesis of atherosclerosis is multifactorial, however the impact of inflammatory cells in this process is well known. Different traditional cardiovascular risk factors (CVRFs) may have specifically different effects on leukocyte subtype. Thus, these special interactions may induce different vascular involvement forms due to the altered endothelial damage and vascular repair mechanisms. The aim of the present study was to investigate whether there is any specific relationship between the leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…As it is known, leukocytes play a pivotal role in atherosclerosis development because their activation is associated with impaired rheological properties, increased expression of adhesion molecules, and overproduction of cytokines, proteolytic enzymes and reactive oxygen species (ROS) [25]. Leukocyte subtypes are correlated with some cardiovascular risk factors: glucose level and arterial hypertension were correlated with neutrophils, uric acid with neutrophils and monocytes, while smoking affected all the subtypes [28]. An elevated neutrophil count correlates with higher risk of ischemic events [26] and with AMI mortality [37].…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, leukocytes play a pivotal role in atherosclerosis development because their activation is associated with impaired rheological properties, increased expression of adhesion molecules, and overproduction of cytokines, proteolytic enzymes and reactive oxygen species (ROS) [25]. Leukocyte subtypes are correlated with some cardiovascular risk factors: glucose level and arterial hypertension were correlated with neutrophils, uric acid with neutrophils and monocytes, while smoking affected all the subtypes [28]. An elevated neutrophil count correlates with higher risk of ischemic events [26] and with AMI mortality [37].…”
Section: Introductionmentioning
confidence: 99%
“…The EPIC-Norfolk study [22] found that the average diameter decrease of HDL was related with the risk increases of CHD. Kocaman [23] found that cardiovascular protection function of HDL2 was stronger compared with HDL3, HDL2 decline in patients with was more evident. This paper divided HDL into 10 subtypes (HDL1-HDL 10) using Lipoprint HDL lipoprotein analyzer, 1-3 types were large particle types (HDL L ), 4-7 types were intermediate particle types (HDL M ), 8-10 types were small particle types (HDL S ).…”
Section: Discussionmentioning
confidence: 99%
“…The PHT designation serves to identify individuals who are potentially at higher risk for developing hypertension (HT) compared to those with optimal BP (< 120/80 mm Hg) (2,3). In the past few years, several prospective and cross-sectional studies have reported an elevated risk of coronary vascular disease (e.g., coronary heart disease and myocardial infarction) in prehypertensive subjects (4)(5)(6)(7)(8). Thus, it is important to understan the pathogenesis of PHT, as PHT may be the fi rst sign of cardiovascular disease (CVD) in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of systemic infl ammatory markers have been found to be associated with the incidence of cardiovascular diseases, such as coronary artery disease, HT, and atrial fi brillation (4,5,11). White blood cell (WBC) count and its subtypes are related to enhanced cardiovascular risk factors (6,12).…”
Section: Introductionmentioning
confidence: 99%